Association of Dry Socket (Alveolar osteitis) with Gender and Site of Extraction (Maxillary and Mandibular): Dry Socket (Alveolar osteitis) and Its Association with Gender and Extraction Site - Ahmed, Zubair; Alam, Jehan; Saddique, Abubakar; Shah, Ruqaya; Azhar, Muhammad Saeed; Rehman, Mehmood Ur; Shar, Mor Khan; Ahmed, Khursheed (Pakistan Journal of Health Sciences, 2026)
American dentist James Young Crawford coined the phrase "dry socket" (Alveolar Osteitis) in 1896 to refer to an acute infection of alveolar bone surrounding the location of a tooth extraction. Severe pain, the lack of a blood clot inside the socket, and food particles inside the socket are clinical indicators of dry socket. Most frequently seen after the extraction of mandibular third molars, the incidence of dry socket ranges greatly, from 1% to over 25%. Objectives: To assess the frequency of dry socket and its association with gender and site of teeth extraction at a tertiary care hospital. Methods: The descriptive cross-sectional study was conducted at the Department of Oral and Maxillofacial Surgery of Jinnah Postgraduate Medical Center, Karachi. Demographic data, such as age and gender, and clinical data, such as the extraction site, smoking status, extraction type and extent, and the frequency of dry socket within five days after extraction. Results: Dry socket was found in 22.5% higher in male, 26.5% compared to female 17.3%. The incidence of dry socket was significantly greater in mandibular extractions 31.1% than in maxillary extractions 8.7% with a p-value of less than 0.01. Smokers exhibited a notably higher rate of dry socket 41.7% compared to non-smokers, 9.7%. Furthermore, 41% of surgical extractions resulted in dry socket, compared to 13.6% of non-surgical extractions. Conclusions: The reported frequency of dry socket was slightly higher in male as compared to female, and it was more commonly observed in patients who underwent mandibular tooth extractions.